The Effectiveness of the Role of the Government Internal Control Apparatus in Efforts to Prevent Corruption - Petrus Klau, Alfonsus; Chariri, Anis (Dinasti Publisher, 2025)
The objectives of this research are to understand the mechanisms and procedures implemented by Government Internal Control Apparatus (APIP) in performing oversight and preventing corruption, and to identify the factors affecting the effectiveness of APIP's role in preventing corruption in government institutions. The method used in this research is qualitative descriptive. In the long term, consistency and sustainability in conducting internal oversight and following up on audit findings are expected to create a clean, transparent, and accountable government. Consequently, public trust in the government will increase, and the management of state resources can be carried out better for the welfare of society. The research has several significant practical contributions. Firstly, this research can help strengthen internal oversight policies and procedures in government institutions. By identifying weaknesses and risks in the existing control system, this research provides concrete recommendations for improvements that can be implemented by the relevant institutions. This will enhance the effectiveness of oversight and reduce the opportunities for corruption. The limitations of research on the effectiveness of the role of government internal control apparatus in preventing corruption often include the limited availability of data and inconsistent quality of reports. Limited or incomplete data collection can affect the accuracy of the assessment of effectiveness and lead to results that do not fully reflect reality.